Pengaruh Media Pembelajaran dan Motivasi Belajar Terhadap Hasil Belajar Mata Pelajaran Ekonomi Siswa MAN 2 Pesisir Selatan - Zuldimon Zuldimon (Journal of Educational Research and Humaniora (JERH), 2023)
The objective of this research is to determine the influence of learning media and learning motivation on the learning outcomes of economics subject among students at MAN 2 Pesisir Selatan. Additionally, the study aims to examine the combined effect of learning media and learning motivation on the learning outcomes of economics subject among students at MAN 2 Pesisir Selatan. The research will be conducted in two stages. The first stage involves a preliminary survey to gather data on the population size and sample to be surveyed. In the second stage, the instrument will be piloted, followed by data collection. The chosen research design is descriptive quantitative. Descriptive research aims to present factual and comprehensive characteristics of the population in a systematic manner. The research will utilize experimental method and random sampling to select a sample of 120 students from the entire population of MAN 2 Pesisir Selatan. Data collection will take place in May 2023 using class questionnaires and direct experiments. The results of this study indicate that learning outcomes are influenced by learning media, as indicated by the F-value = 0.000 < 0.05. Further testing of the learning media is shown by the t-value = 0.000 < 0.05. This confirms that the learning outcomes of the economics subject improve when measured against explanatory media. The learning outcomes of the economics subject are influenced by learning motivation, as indicated by the F-value = 0.000 < 0.05. Further motivation tests also show a t-value = 0.000 < 0.05.